Francisco Suárez’s Encounter with Calvin Over Human Freedom - Salas Victor M. (Perichoresis: The Theological Journal of Emanuel University, 2020)
This essay explores Francisco Suárez’s account of the nature of human free will. To that end, Suárez’s engagement with John Calvin is considered so as to place the Jesuit’s account into greater relief. The conclusion of this study will reveal that, for Suárez, the human will’s freedom of self–determination is both caused by God and consists in its own indifference regarding the power to act and the power not to act.